2022
DOI: 10.1155/2022/7378379
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation Techniques for Ram Sperm

Abstract: Germplasm storage and transportation in artificial insemination (AI) and other advanced technologies are facilitated by cryopreservation. In reproduction, the cryopreservation of sperm allows it to be transported across vast distances and used even after the sire’s death. However, the technique of cryopreservation might damage sperm and limit their activity. Several cryobiological investigations have reported that the integrity of the sperm membrane is frequently involved in the physical and biological element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 131 publications
(166 reference statements)
0
8
0
Order By: Relevance
“…Vozaf et al [27] reported an IM decrease of 15.1-18.4% in their study, but a variation of 15 to 28% was observed in the Merino ram (Spain) according to three freezing methodologies [30], and up to 49.1% in Manchega rams (Spain) [31]. In a recent review considering more than 20 ram breeds, the IM decrease in thawed SPZ varied between 22.7% and 74.6% [32]. Probably, breed differences in seminal traits of frozen semen may be explained by inherent susceptibilities of SPZ cells to the deleterious effects of cryopreservation and evaluation methods used in the different studies [33].…”
Section: Discussionmentioning
confidence: 87%
“…Vozaf et al [27] reported an IM decrease of 15.1-18.4% in their study, but a variation of 15 to 28% was observed in the Merino ram (Spain) according to three freezing methodologies [30], and up to 49.1% in Manchega rams (Spain) [31]. In a recent review considering more than 20 ram breeds, the IM decrease in thawed SPZ varied between 22.7% and 74.6% [32]. Probably, breed differences in seminal traits of frozen semen may be explained by inherent susceptibilities of SPZ cells to the deleterious effects of cryopreservation and evaluation methods used in the different studies [33].…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, preserved semen has become an important tool for genetic improvement and has streamlined semen transport. Therefore, the dilution and cooling of semen play crucial roles in inseminating multiple females and providing essential nutrients and protection against pH changes [ 85 ]. Extensive studies have investigated this topic using several extenders.…”
Section: Exogenous Factorsmentioning
confidence: 99%
“…Besides, it increases insemination's speed in the field (Yang et al, 2018). However, during liquid storage, the accumulation of reactive oxygen species (ROS) and the oxidation of sperm plasma membrane cause changes in the spermatozoa and decrease the sperm quality and fertility (Allai et al, 2018; Saha et al, 2022). To avoid such negative effects, the inclusion of antioxidants in extenders can minimize the negative effect of ROS and maintain sperm quality after liquid storage (Alenezy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%